Protocols of the Society of Polish Craftsmen in Zielona Góra as an organized report from the meeting - Żuraszek-Ryś, Iwona (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
The reflections on the methods of applying the style features specific to the protocol by the persons elaborating reports on the course of the meetings of the Society of Polish Craftsmen in Zielona Góra discussed in this paper, and thus their linguistic expression in the scope of style, ability to fit into a genre convention, are aimed at responding to the question: whether the analyzed documents can be considered as a structured report from the meeting.